Perempuan Masa Kini Melek Teknologi - Hidayat, Andi Nurul (Musawa: Journal for Gender Studies, 2017)
Indonesian women both in the ministries, companies, organizations, social agencies, entrepreneurs, activists, and show that women have an important role in Indonesia, one of which is the positive impact women today in the use of technology is significant growth and development increased over the months and years gave birth to innovation and facilitate the community this is also felt by women or women that trend smartphone technology to the netbook at this time can be used, this side of the business and may make women make tips and guides, as well as solutions for example also hijab better known as the tutorial hijab among women of today, used to explore the creativity of women to use the hijab and the internet is helpful in the information, then here is said to be women of today are technology literate simplicity is very beneficial to the world of technology and fashion. With the new technology used in the field of information and communication, especially the Internet has brought the world into the new era.